Law as a means ofthe formation of legal globalization and legal awareness in civil society - Savenko, Viktor (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
This article researches the features of formation of legal awareness of citizens in a civil society; the interdependence and interinfluence of law, legal awareness and legal culture have been analysed; modern concepts of legal awareness have been studied; the fundamental principles of formation of legal awareness in terms of legal harmonisation of modern Ukrainian society have been researched.